The Influence of Social Media on Policy Issues Central Java Government - El Adawiyah, Sa'diyah; Hermanto, Agus; Patrianti, Tria (Jogjakarta Communication Conference (JCC), 2025)
The use of social media as a new media era, which is also often referred to as the digital era, is digitalized. This study was conducted using a quantitative approach through surveys. The study runs from May to June 2024 at all stages, including the collection of primary data in the field. This study produced the main findings, among others: the community is not sufficiently exposed to various issues related to development programs or policies because only about 15.8% of the people of Central Java have been exposed to program/policy issues carried out by the Government in the last three years. The social assistance program (bansos) has received the highest public recognition compared to other programs, in line with the existence of the Social Assistance program which is run by the government very intensively to support the underprivileged. Public exposure to various types of social media and information channels owned by the Central Java Provincial Government is also relatively low. However, the level of public visits to social media and existing information channels is relatively good. The community also gives a relatively good assessment of the services provided by the managers of existing social media accounts, because they provide adequate responses and services for the various forms of interaction they make. Likewise, complaints, although still on a small scale, but the response given by officers or policy managers to the problems they complained about is considered very satisfactory.